2016
DOI: 10.1097/brs.0000000000001327
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Is an Independent Risk Factor of Early Complications After Revision Spine Surgery

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 85 publications
1
25
0
1
Order By: Relevance
“…The preoperative risk factors identified in the present study have been demonstrated in the spine surgery literature with regard to other surgical interventions. Obesity, for example, is a well-supported risk factor for post-treatment complications [14,15]. In the present study, obesity was a major risk factor (53% greater odds) for MMM after SRS for spinal metastases.…”
Section: Discussionsupporting
confidence: 53%
“…The preoperative risk factors identified in the present study have been demonstrated in the spine surgery literature with regard to other surgical interventions. Obesity, for example, is a well-supported risk factor for post-treatment complications [14,15]. In the present study, obesity was a major risk factor (53% greater odds) for MMM after SRS for spinal metastases.…”
Section: Discussionsupporting
confidence: 53%
“…Moreover, race/ethnicity was not associated with differential outcomes, despite the fact that disparities are well-known in oncology patients. 31 While obesity has been shown to be associated with adverse events among patients undergoing surgery for degenerative spinal conditions, 89 in this analysis body habitus was not associated with differential outcomes. Additionally, neither complications during the surgical hospitalization nor discharge disposition were predictive of readmission.…”
mentioning
confidence: 71%
“…To more fully explore in impact of obesity on the entire spine, Teraguchi et al [24] investigated the prevalence and distribution of intervertebral disc degeneration over the entire spine and found the age and obesity were associated with the presence of disc degeneration in all areas of the spine, indicating that obesity places stress across multiple regions of back. BMI and obesity have also been identified as a risk factor for adjacent segment diseases and post-operative complications among patients undergoing lumbar fusion for degenerative spine diseases [30,31,32,33,34,35,36,37,38,39,40]. Weight control before and after the surgery was observed to reduce the incidence of adjacent segment disease and improve the fusion surgery outcome [41,42].…”
Section: Introductionmentioning
confidence: 99%